Hubungan Antara Perilaku Pencarian Informasi Terhadap Perilaku Inovatif Mahasiswa di UPT Perpustakaan Universitas Hasanuddin - Jamaluddin Jamaluddin; La Tommeng (Perpustakaan Nasional, 2021)
This study aims to determine information-seeking behavior and innovative behavior of final year students in compiling scientific papers (tesis, dissertation) at the Hasanuddin University Library (UNHAS). Primary data obtained through questionnaires. The population in this study were all visitors who visited the UPT Library of UNHAS totaling 420 people per day. The number of samples for 81 people was calculated using the Slovin formula. The data analysis used was simple linear regression to prove the influence between the Information Seeking Behavior and Student Innovative Behavior variables in the UPT Library of UNHAS. This study found information seeking behavior has a positive and significant correlation with innovative behavior, at a strong correlation level (0.762). The character of students with innovative behavior is shown in searching for information, such as finding out the latest technology can be used to obtain the required reference source information. Another character found is shown in students' efforts to obtain the information directly from the original source through various networks and communication media. Indicators of information utilization due to the need to compile a final project proved to be the strongest predictor of innovative behavior. Meanwhile, indicators were found that there were less innovative students coming up with new ideas in information seeking, therefore it is recommended to escalate the student information literacy and library education by including information retrieval techniques.